Sex Differences in the Relationship Between Body Composition and Masld Progression in a Murine Model of Metabolic Syndrome - Carvalho Da Silva-Xavier, A (Elsevier Inc., 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) progression exhibits significant sex differences, with males generally developing more severe disease. This study used an endothelial nitric oxide synthase knockout (eNOS KO) murine model to investigate sex-specific MASLD progression under a Western diet intervention. Magnetic resonance imaging (MRI) assessed body composition and liver and skeletal muscle fat fraction, revealing greater visceral fat, liver volume, and liver-to-muscle fat ratios in males. Dimensionality reduction and clustering analyses identified distinct sex-specific MASLD phenotypes and progression patterns. Histological evaluations confirmed greater liver damage in males, evidenced by higher MAFLD Activity Scores. These findings highlight the critical role of sex as a biological variable in MASLD pathology and emphasize the influence of body composition and fat distribution on disease progression. The study underscores the utility of advanced imaging and analytical techniques for refining non-invasive diagnostics and guiding sex-specific interventions, paving the way for personalized MASLD management strategies. © 2025 The Authors